Kajian Kritis Pemikiran Epistemologi Frithjof Schuon (1907–1998) - Dinar Dewi Kania (Universitas Darussalam Gontor, 2014)
The purpose of this article is to construct and employ a critical study to Frithjof Schuon’ thought on epistemology which includes the nature of knowledge, the object of knowledge and the process of acquiring knowledge. This study is a literature research which utilize his scientific works both primary and secondary sources. The results showed that Schuon epistemology could not eluded the paradigm of Western dualism as truth and certainty viewed double, which are relative truth and absolute truth. Relative truth and certainty of the truth according to Schuon are obtained through religious dogma, but the total truth and certainty of ‘being’ could only be obtained through spiritual realization, namely gnosis or metaphysics. Thus, religious knowledge status which derived from revelation is lower than the metaphysical knowledge derived from the intellect through meditation. It is conclude that Schuon’s view is very much contrary to the principles of Islamic epistemology. Islam has asserted al- Qur’an as an authentic revelation from Allah SWT and acknowledged it as the highest source of knowledge. Epistemology of Islam never affirms the necessity of spiritual realization through meditation to enhance the revelation.